Hipótesis de la exclusión de linajes: Una alternativa para el desarrollo de cultivares de arroz con resistencia durable a Pyricularia grisea (Sacc) en Colombia - Prado Patiño, Gustavo A.; Correa Victoria, Fernando J.; Aricapa, María Girlena; Tulande Valencia, Edgar; Escobar, F. (1999)
Rice blast caused by the fungus Pyricularia grisea (Sacc.) is the most important disease of rice crops throughout the world. The development of resistant varieties is the method preferred by breeders for the control of the disease; however, varieties tend to become susceptible in periods ranging from one to two years after their deployment. The great variability of the pathogen is mentioned as the cause o F the breaking down of the resistance. More than 50 races grouped mainly into six genetic families named from SRL-1 to SRL-6, have been reported to exist in Colombia. The combination of complementary resistance genes between genetic families in varieties of more durable resistance conveniently evaluated is the correct way. This research, carried out under controlled greenhouse and field conditions, has been to study the reaction to the pathogen populations in Colombia of the progenies resulting from the cross between C 101 LAG x C 101 A51 from IRRI which contain the Pi-1 and the Pi-2 resistance genes, respectively. Pi-1 gene showed compatibility with the SRL-5 genetic families and the Pi-2 gene with genetic families 1, 2, 4, and 6. A total of 109 lines obtained from the simple cross between the two isogenic lines were tested up to the F6 generation for their reaction to rice blast. These lines were inoculated with 19 isolates, 15 of which represent the six genetic families of the fungus, the four remaining isolates had not been previously classified. The results obtained showed that 19 lines (17.4%) resulted to be resistant under field conditions as well as to the six lineages of the greenhouse inoculations, indicating that the Pi-1 and Pi-2 gene combination confers resistance to the whole P. grisea population of Colombia. The lines selected in this study for the complete resistance to Pyricularia must be tested in further generations in order to confirm the stability of resistance to blast, and should be incorporated in breeding programs for future commercials varieties.